Attractiveness Is Multimodal: Beauty Is Also in the Nose and Ear of the Beholder - Groyecka, Agata; Pisanski, Katarzyna; Sorokowska, Agnieszka; Havlíček, Jan; Karwowski, Maciej; Puts, David; Roberts, S. Craig; Sorokowski, Piotr (Frontiers in Psychology, 2017)
Attractiveness plays a central role in human nonverbal communication and has been broadly examined in diverse subfields of contemporary psychology. Researchers have garnered compelling evidence in support of the evolutionary functions of physical attractiveness and its role in our daily lives, while at the same time, having largely ignored the significant contribution of non-visual modalities and the relationships among them. Acoustic and olfactory cues can, separately or in combination, strongly influence the perceived attractiveness of an individual and therefore attitudes and actions toward that person. Here, we discuss the relative importance of visual, auditory and olfactory traits in judgments of attractiveness, and review neural and behavioral studies that support the highly complex and multimodal nature of person perception. Further, we discuss three alternative evolutionary hypotheses aimed at explaining the function of multiple indices of attractiveness. In this review, we provide several lines of evidence supporting the importance of the voice, body odor, and facial and body appearance in the perception of beauty and mate preferences, and therefore the critical need to incorporate cross-modal perception and multisensory integration into future research on human physical attractiveness.